2011
DOI: 10.1038/nature10258
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human centromeric nucleosome containing CENP-A

Abstract: In eukaryotes, accurate chromosome segregation during mitosis and meiosis is coordinated by kinetochores, which are unique chromosomal sites for microtubule attachment. Centromeres specify the kinetochore formation sites on individual chromosomes, and are epigenetically marked by the assembly of nucleosomes containing the centromere-specific histone H3 variant, CENP-A. Although the underlying mechanism is unclear, centromere inheritance is probably dictated by the architecture of the centromeric nucleosome. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
511
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(572 citation statements)
references
References 38 publications
52
511
4
1
Order By: Relevance
“…The notion that CENP-A can function as a hemisome will not be corroborated until a hemisome is successfully isolated and characterized biochemically. In contrast to a CENP-A hemisome, the crystal structure of an octameric CENP-A nucleosome has been resolved, revealing only subtle differences to canonical octameric H3 nucleosomes (Tachiwana et al 2011). Octameric CENP-A nucleosomes wrap slightly less DNA than H3 nucleosomes ( 120 bp vs. 147 bp), resulting in different DNA entry/exit angles from the nucleosome, and several exposed residues exist in CENP-A's extended loop 1 region that are important for CENP-A nucleosome stability (Tachiwana et al 2011).…”
Section: The Structure Of Cenp-a-containing Nucleosomesmentioning
confidence: 99%
See 3 more Smart Citations
“…The notion that CENP-A can function as a hemisome will not be corroborated until a hemisome is successfully isolated and characterized biochemically. In contrast to a CENP-A hemisome, the crystal structure of an octameric CENP-A nucleosome has been resolved, revealing only subtle differences to canonical octameric H3 nucleosomes (Tachiwana et al 2011). Octameric CENP-A nucleosomes wrap slightly less DNA than H3 nucleosomes ( 120 bp vs. 147 bp), resulting in different DNA entry/exit angles from the nucleosome, and several exposed residues exist in CENP-A's extended loop 1 region that are important for CENP-A nucleosome stability (Tachiwana et al 2011).…”
Section: The Structure Of Cenp-a-containing Nucleosomesmentioning
confidence: 99%
“…In contrast to a CENP-A hemisome, the crystal structure of an octameric CENP-A nucleosome has been resolved, revealing only subtle differences to canonical octameric H3 nucleosomes (Tachiwana et al 2011). Octameric CENP-A nucleosomes wrap slightly less DNA than H3 nucleosomes ( 120 bp vs. 147 bp), resulting in different DNA entry/exit angles from the nucleosome, and several exposed residues exist in CENP-A's extended loop 1 region that are important for CENP-A nucleosome stability (Tachiwana et al 2011). In support of the octameric CENP-A nucleosome model, ChIP-Seq data revealed that CENP-A mononucleosomes wrap more DNA in cells than hemisomes could wrap (Hasson et al 2013), immunoprecipitation of Drosophila CENP-C CID mononucleosomes revealed the presence of CENP-A CID dimers (Zhang et al 2012), and CAL1-assembled CENP-A CID nucleosomes in Drosophila are octameric .…”
Section: The Structure Of Cenp-a-containing Nucleosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…A large majority of nucleosome crystal structures are based on a palindromic 73 bp region from the human alpha satellite repeat (Harp et al 1996). However, the functionally relevant nucleosome positioning is unclear and complicated by active debate over the repeating chromatin unit size, the wrapping topology, and whether relevant centromeric chromatin is wrapped as either H3 and CENP-A containing nucleosomes or both (Tachiwana et al 2011), or possibly even other histone fold structures of centromeric proteins (Nishino et al 2012).…”
Section: Alpha Satellite Dnamentioning
confidence: 99%